On the best means of raising the supplies for a war expenditure - Cairnes, John E. (Statistical and Social Inquiry Society of Ireland, 1854)
The question respecting the raising of the supplies for a war expenditure, by what means they can be most efficiently obtained, and with the least inconvenience to the community, has been of late years allowed to fall in some degree into abeyance; owing, perhaps, to the small probability there seemed of there being any occasion for bringing it to a practical decision. It appears, however, that it is not likely to enjoy this exemption from discussion much longer. On the contrary, there seems now to be little doubt that the financial problem of a war expenditure will soon assume a character of formidable and pressing importance; and under these circumstances, a brief notice of this question, and of some of the arguments and statistics applying to it, may perhaps possess some interest for this society.
Read March 20th 1854
Keywords: War expenditure; Fundraising; 314.15